(3TQM dGejI GdCaYGds - (3HOQ GdOjf eMeO Hf eMeO Hf YHO Gddg Hf eGdc GdWGFis; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3gPg ChQGb JTJed Ydi bUjOI hGdOi QMeg Gddg ai CHfjI GdCaYGd heG jJUd HgG s
(3BNQgG (B:s
(3EfJgJ GdbUjOI hTQMgG hGdMeO ddg Ydi cd MGd hdG Mhd hdG bhI EdG HGddg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdUQas